The life and activity of Vaclovas Biržiška in 1940 - 1945 - Silvija Stakulienė (Knygotyra)
V. Biržiška's activities are noted in the archival documents that can be found in the manuscripts departments of the libraries of Vilnius University and the Academy of Sciences, as well as in the Central State Archives.